Mitigation of hallucination and interpretations of self attention of Mistral 7B AI to analyze and visualize context understanding ability of large language models - Taki, S.M. Abrar Mustakim; Kar, Showmick; Niloy, Soumik Deb; Rakib, Mazharul Islam; Biswas, Abdullah Al Nahid (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.